8-(DIMETHYLAMINO)-N,N-DIMETHYLNAPHTHALEN-1-AMINIUM AND HYDROGENTEREPHTHALATE AS SYNTHONS FOR SUPRAMOLECULAR ARCHITECTURE - Andres Vega; Duval Donoso; Carolina Muñoz; Nicolás Aravena (Journal of the Chilean Chemical Society, 2023)
8-(dimethylamino)-N,N-dimethylnaphthalen-1-aminium hydrogenterephthalate (PSH+TPAH-) and 8-(dimethylamino)-N,N-dimethylnaphthalen-1-aminium hydrogen-terephthalate hydrate (PSH+TPAH-·H2O) were prepared by the direct reaction of N1,N1,N8,N8-tetramethylnaphthalene-1,8-diamine, Proton Sponge (PS) © and terephthalic acid (TPAH2) in a 1:1 stoichiometric relation. The structure of both salts is constructed on the base of 1D chains defined by hydrogen bonding of the anionic carboxylate end and the carboxylic acid of TPAH- anion. Additionally for the structure of PSH+TPAH-·H2O the water molecules connect this 1D chains through hydrogen bonds, then defining a 1D-belt. In both cases the PSH+ provides balance of charge among the chains.